Spironolactone may provide protection from SARS-CoV-2: Targeting androgens, angiotensin converting enzyme 2 (ACE2), and renin-angiotensin-aldosterone system (RAAS) - Cadegiani, Flavio A. (Med Hypotheses, 2020)
In coronavirus disease-19 (COVID-19), four major factors have been correlated with worse prognosis: aging, hypertension, obesity, and exposure to androgen hormones. Angiotensin-converting enzyme-2 (ACE2) receptor, regulation of the renin-angiotensin-aldosterone system (RAAS), and transmembrane serine protease 2 (TMPRSS2) action are critical for the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) cell entry and infectivity. ACE2 expression and RAAS are abnormal in hypertension and obesity, while TMPRSS2 is overexpressed when exposed to androgens, which may justify why these factors are overrepresented in COVID-19. Among therapeutic targets for SARS-CoV-2, we hypothesized that spironolactone, a long used and safe mineralocorticoid and androgen receptors antagonist, with effective anti-hypertensive, cardioprotective, nephroprotective, and anti-androgenic properties may offer pleiotropic actions in different sites to protect from COVID-19. Current data shows that spironolactone may concurrently mitigate abnormal ACE2 expression, correct the balances membrane-attached and free circulating ACE2 and between angiotensin II and Angiotensin-(1-7) (Ang-(1-7)), suppress androgen-mediated TMPRSS2 activity, and inhibit obesity-related RAAS dysfunctions, with consequent decrease of viral priming. Hence, spironolactone may provide protection from SARS-CoV-2, and has sufficient plausibility to be clinically tested, particularly in the early stages of COVID-19.